Consolidative thoracic radiotherapy in stage IV small cell lung cancer: Selection of patients amongst European IASLC and ESTRO experts. (June 2019) - Putora, Paul Martin; Glatzer, Markus; De Ruysscher, Dirk; Faivre-Finn, Corinne; Belderbos, José; Besse, Benjamin; Blackhall, Fiona; Califano, Raffaele; Cappuzzo, Federico; de Marinis, Filippo; Dziadiuszko, Rafal; Felip, Enriqueta; et al.
Highlights: Experts from IASLC and ESTRO recommend consolidative TRT in selected patients with stage IV SCLC. TRT was recommended primarily for fit patients responding to chemotherapy. The highest agreement for TRT was seen in patients with complete remission extrathoracically and a partial remission intrathoracically. Medical and radiation oncologists provided similar recommendations in most cases. Abstract: Background: The role of consolidative thoracic radiotherapy (TRT) in stage IV small cell lung cancer (SCLC) is not uniformly accepted. Methods: We obtained a list of 13 European medical oncologists from the International Association for the Study of Lung Cancer (IASLC) and 13 European radiation oncologists from the European Society for Therapeutic Radiation Oncology (ESTRO). The strategies in decision making for TRT in stage IV SCLC were collected. Decision trees were created representing these strategies. Frequencies of recommending TRT were analysed for various parameter combinations based on the objective consensus methodology. Results: The factors associated with the recommendation for TRT included fitness of the patient, limited extrathoracic tumour burden, initial bulky thoracic disease and response to chemotherapy. The highest consensus for TRT was in fit patients with limited extrathoracic tumour burden and initial bulky disease with either a complete extrathoracic response or partial thoracic response (92% recommend TRT). For these patients the recommendations were the same for medical and radiation oncologists. In the setting of partial response (intra- and extra-thoracically) without initial bulky thoracic disease radiation oncologists were more likely to recommend TRT than medical oncologists. For unfit patients or for patients with poor overall response to chemotherapy, the majority did not recommend TRT. Conclusion: European radiation and medical oncologists specializing in lung cancer recommend TRT in selected patients with stage IV SCLC and restrict its use primarily to fit patients who responded to chemotherapy with limited extrathoracic tumour burden.